(untitled) (Diametros, 2008)
The paper discusses modal realism, as expounded by David Lewis, and points out some crucial difficulties of this wide-ranging philosophical position. An essential component of it is the counterpart theory, which has the unfortunate consequence of eliminating trans-world objects from our ontology. And this leads to an enormously anomalous behavior of proper names in modal sentences, seriously undermining the plausibility of modal realism.